Steroid Alkaloids from Holarrhena africana with Strong Activity against Trypanosoma brucei rhodesiense - Nnadi, Charles Okeke (Molecules, 2017)
In our continued search for natural compounds with activity against Trypanosoma brucei, causative agent of human African trypanosomiasis (HAT, “sleeping sickness”), we have investigated extracts from the leaves and bark of the West African Holarrhena africana (syn. Holarrhena floribunda; Apocynaceae). The extracts and their alkaloid-enriched fractions displayed promising in vitro activity against bloodstream forms of T. brucei rhodesiense (Tbr; East African HAT). Bioactivity-guided chromatographic fractionation of the alkaloid-rich fractions resulted in the isolation of 17 steroid alkaloids, one nitrogen-free steroid and one alkaloid-like non-steroid. Impressive activities (IC(50) in µM) against Tbr were recorded for 3β-holaphyllamine (0.40 ± 0.28), 3α-holaphyllamine (0.37 ± 0.16), 3β-dihydroholaphyllamine (0.67 ± 0.03), N-methylholaphyllamine (0.08 ± 0.01), conessimine (0.17 ± 0.08), conessine (0.42 ± 0.09), isoconessimine (0.17 ± 0.11) and holarrhesine (0.12 ± 0.08) with selectivity indices ranging from 13 to 302. Based on comparison of the structures of this congeneric series of steroid alkaloids and their activities, structure-activity relationships (SARs) could be established. It was found that a basic amino group at position C-3 of the pregnane or pregn-5-ene steroid nucleus is required for a significant anti-trypanosomal activity. The mono-methylated amino group at C-3 represents an optimum for activity. ∆(5,6) unsaturation slightly increased the activity while hydrolysis of C-12β ester derivatives led to a loss of activity. An additional amino group at C-20 engaged in a pyrrolidine ring closed towards C-18 significantly increased the selectivity index of the compounds. Our findings provide useful empirical data for further development of steroid alkaloids as a novel class of anti-trypanosomal compounds which represent a promising starting point towards new drugs to combat human African trypanosomiasis.